1998
DOI: 10.1038/sj.jhh.1000563
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal oestrogen reduces daytime blood pressure in hypertensive women

Abstract: The aim of this study was to investigate the acute effects of transdermally administered 17-␤-oestradiol on ambulatory blood pressure (BP) in hypertensive, postmenopausal women. Thirteen postmenopausal women with ongoing treatment for hypertension were included in this placebo-controlled, double-blind cross-over study. Ambulatory recordings of BP and heart rate were performed during 24 h on two occasions, separated by at least 1 week, after application of a patch containing either 100 g per 24 h 17-␤-oestradio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 32 publications
3
22
0
2
Order By: Relevance
“…Journal of Human Hypertension in agreement with the hypothesis that oestrogen deprivation, either at the onset of menstruation 27 or in non-substituted postmenopausal normotensive [23][24][25] or hypertensive 22 women, may increase blood pressure. Oestrogens change the loading conditions on the elastin or collagen fibres or alter the structure of the vessel wall.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Journal of Human Hypertension in agreement with the hypothesis that oestrogen deprivation, either at the onset of menstruation 27 or in non-substituted postmenopausal normotensive [23][24][25] or hypertensive 22 women, may increase blood pressure. Oestrogens change the loading conditions on the elastin or collagen fibres or alter the structure of the vessel wall.…”
Section: Discussionsupporting
confidence: 86%
“…18 Other studies are in keeping with our findings, but did not correct for the level of blood pressure [19][20][21] or reported that withdrawal of hormonal replacement therapy for 4 weeks resulted in a decrease of systemic arterial compliance and an increase in pulse wave velocity in the femoralisdorsalis pedis region, but not in the aorto-femoral territory. 21 Recent studies using ambulatory monitoring [22][23][24][25][26] or automated blood pressure self-measurement 27 are…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this area there is a paucity of data. In this issue of the Journal of Human Hypertension, Manhem et al 13 have demonstrated a 3 mm drop in daytime blood pressure among pre-existing hypertensive subjects given transdermal oestrogen. The effect, although modest, represents an important observation as it is one of the few prospective randomised trials of HRT in hypertensives in which blood pressure is the primary clinical end-point.…”
Section: Why Should Hrt Effect Blood Pressure?mentioning
confidence: 97%
“…4 Little information is available regarding the long-term effects of HRT in hypertensive women, but short duration studies in hypertensive women have demonstrated either a neutral or even modest hypotensive effect. [5][6][7][8][9][10] Cyclical HRT preparations are unacceptable to most women suffering from coronary disease or hypertension. Tibolone is a novel steroid compound, which controls menopausal symptoms, 11 inhibits postmenopausal bone loss 12 and augments forearm blood flow.…”
Section: Introductionmentioning
confidence: 99%